The impulse factor : why some of us play it safe and others risk it all - Tasler, Nick, 1978- (New York : Simon & Schuster, 2008)
Tasler teaches readers how to thrive when faced with difficult choices, provides a clear understanding of why you make the choices you do, and suggests the tools to make those decision change your business and your life.
Origin of seekers : from caveman to cage fighters -- Impulsivity's hidden side : the secret of being directionally correct -- Eat or be eaten : what politicians have learned from primates -- Bubblology : the plague of the $76,000 flower -- Common sense of ownership -- Factoring you into your decisions -- Potential seekers : exploring the connection between sinners, saints, barbies, and farmers -- Risk managers : conquering the fear of big cats -- Striking a balance -- Afterword : putting big ideas to the test.
"A Fireside book."
Incluye referencia bibliográficas (páginas [249]-256).
Keywords: ELECCION (PSICOLOGIA); IMPULSIVIDAD